Improving food adequacy low-value collagencontaining raw materials in the technology of semi-finished products - Horishnii, Pavlo; Topchiy, Oksana; Shevchenko (Kishenko), Iryna; Kotlyar, Eugene; Petrina, Alla (My University, 2021)
The modern development of technologies at meat processing enterprises is aimed at finding ways to rationally use low-value meat protein-containing raw materials and create innovative technologies for the production of organic food. In the scientific and technological aspect, the issues of improving the efficiency of natural resources are reduced to the development and implementation of low- and zero-waste resources and energy-saving technologies, which provide the most complete, efficient use of resources and principles of a waste-free, environment. Сучасний розвиток технологій на м’ясопереробних підприємствах спрямований на пошук шляхів раціонального використання малоцінної м’ясної білковмісної сировини та створення інноваційних технологій виробництва органічних продуктів харчування. У науково-технологічному аспекті питання підвищення ефективності використання природних ресурсів зводяться до розробки та впровадження мало- та безвідходних ресурсо- та енергозберігаючих технологій, які забезпечують найбільш повне, ефективне використання ресурсів та принципів безвідходне середовище.
Keywords: кафедра технології м’яса і м’ясних продуктів; waste-free production; collagen-containing raw materials; waste-free production; колагеновмісна сировина; напівфабрикати; безвідходне виробництво